Isolation and Molecular Identification of Cadmium-Resistant Bacteria from Paddy Soil in the Tallo Watershed, Makassar - Nurhikmayani, Risky; Dewi, Aghis Sukma (Al-Hayat: Journal of Biology and Applied Biology, 2025)
Cadmium contamination of paddy soils is a global concern because Cd can accumulate in rice through nutrient absorption, posing a food safety risk. More than a quarter of the Tallo watershed area, Makassar is a rice field that is vulnerable to pollution due to industrial activities and water runoff from urban areas. This study aims to isolate and identify Cd-resistant bacteria from paddy field soils in the Tallo watershed to find potential isolates that have the potential for bioremediation. The soil samples collected were from the rhizosphere of rice fields in the Tallo watershed, which were varying distances from the Tallo Main River. Bacterial isolation used nutrient agar media, followed by Cd resistance testing using Nutrient Agar-CdCl₂ media with increasing concentrations from 10 mg L-1 to 110 mg L-1. Molecular identification was carried out on the most Cd-tolerant isolates using the 16S rRNA marker gene with primers 27F and 1492R. From the isolation, 22 isolates were obtained, with 19 isolates resistant to CdCl2 10 mg L-1; Only five isolates could continue growing at a concentration of 100 mg L-1, and only one isolate could grow up to a concentration of 110 mg L-1; the isolate was L1(4). The isolate L1(4) exhibited the best growth and was identified as Aeromonas veronii through 16S rRNA gene sequencing. These findings highlight Aeromonas veronii as a promising candidate for the bioremediation of Cd-contaminated soils in the Tallo watershed